Preparing the Bone Tissue Regeneration Ground by Exosomes: From Diagnosis to Therapy - Batla Al-Sowayan (Molecules, 2020)
Bone tissue engineering employs acellular scaffolds or scaffolds, along with cells and growth factors, to provide the mechanical support needed, as well as serve as a delivery vehicle for bioactive molecules to the injury sites. As tissue engineering continues to evolve, it has integrated two emerging fields: stem cells and nanotechnology. A paracrine factor that is found to be responsible for the major regenerative effect in stem cell transplantation is an extracellular vesicle called an ‘exosome’. Recent advances in nanotechnology have allowed the ‘exosome’ to be distinguished from other extracellular vesicles and be polymerized into a well-defined concept. Scientists are now investigating exosome uses in clinical applications. For bone-related diseases, exosomes are being explored as biomarkers for different bone pathologies. They are also being explored as a therapeutic agent where progenitor cell-derived exosomes are used to regenerate damaged bone tissue. In addition, exosomes are being tested as immune modulators for bone tissue inflammation, and finally as a delivery vehicle for therapeutic agents. This review discusses recently published literature on the clinical utilization of exosomes in bone-related applications and the correlated advantages. A particular focus will be placed on the potential utilization of regenerative cell-derived exosomes as a natural biomaterial for tissue regeneration.